Human Dignity as a Sui Generis Principle. (26th December 2019) - Riley, Stephen
Abstract: This paper argues that human dignity is a sui generis status principle whose function lies in unifying our normative orders. More fully, human dignity denotes a basic status to be preserved in any institution or process; it is a principle demanding determination in different contexts; and it has its most characteristic application where the legal, moral, and political place competing obligations on individuals. The implication of this account is that we should not seek to reduce human dignity to either a legal norm or a legal principle.